ANALISIS FAKTOR-FAKTOR FUNDAMENTAL YANG BERPENGARUH TERHADAP RETURN SAHAM SYARIAH PADA PERUSAHAAN YANG TERGABUNG DALAM JAKARTA ISLAMIC INDEX (JII) - Fitri . (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2018)
The development of the sharia capital market in Indonesia until 2016 shows that Islamic stock shares do not yet have optimal and consistent performance in terms of the returns given. Fundamental analysis is a study that studies matters relating to the finances of a business with a view to better understanding the basic nature and operational characteristics of public companies that issue shares. Accounting information or company financial statements can be used as a factor of fundamental analysis based on real data that is useful for evaluating and projecting the value of a stock. The purpose of this study was to determine the effect of return on assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Earning per share (EPS), Total asset turn over (TATO) on Islamic stock returns. The research method used is descriptive verification. The unit of analysis in this study is Islamic stocks that are members of the Jakarta Islamic Index (JII). Statistical test analysis in this study using multiple linear regression analysis, t test and F test. The results showed that the variables ROA, CR, EPS and TATO have a positive and significant effect on Islamic stock returns, but the DER variable does not have a significant effect on stock returns. sharia. Keywords: return on asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Earning per share (EPS), Total assets turn over (TATO),